Carbothermal reduction of iron oxides under electromagnetic influence - Grishin , O.M.; Velychko , O.G.; Grek , O.S.; Nadtochiy , A.A. (Theory and Practice of Metallurgy, 2024)
Objective. To obtain quantitative characteristics of the effect of the electromagnetic field on the process of reduction of iron oxides by carbon in the solid phase and to study the mechanism of this process, experimental studies of carbon-thermal and complex reduction of iron from hematite, magnetite, and rolling scale were carried out. Methods. The experiments were carried out in an alternating magnetic field of an induction furnace with an alternating current frequency in the inductor from 50 Hz to 40 kHz using the thermogravimetric technique. The reduction process was modelled under conditions of carbothermal reduction with the determination of the final degree of oxide reduction and the reduction time in the temperature range of 973-1373 K using various ore-coal materials. Results. The obtained data indicate an acceleration of carbon gasification and gas oxide reduction processes under the influence of EMF by 10-20 %. It was found that the influence of the magnetic field is higher the higher the frequency of the alternating current in the furnace inductor and that the influence of the magnetic field is higher in the low-temperature reduction ranges. Scientific novelty. The effect of EMF on the kinetics of iron oxides reduction has been experimentally confirmed. The mechanism of the field effect intensifying the iron reduction process is proposed. Practical significance. The intensification of the processes of carbon-thermal reduction of iron oxides provides a reduction in energy consumption and an increase in process productivity.